PEMANFAATAN JAMU HERBAL UNTUK MENINGKATKAN IMUNITAS TUBUH DI ERA PANDEMI COVID-19 - Artini, I.G.A.; Trapika, I.G.M.G.S.C.; Dewi, N.W.S.; Indrayani, A.W.; Sumardika, I.W.; Jawi, I.M.; Satriyasa, B.K.; Aman, I.G.M.; Mahendra, A.N.; Widhiartini, I.A.A.; Ernawati, D.K. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana Mengabdi, 2023)
To date, COVID-19 infection still become an important health problem in Indonesia, including Bali. We may concern about this situation since there has been no specific drug or vaccine available against COVID-19 infection. In this new normal era, we should maintain our immunity to prevent the infection. Some herbs potentially possess great effect on maintaining immunity to protect ourselves from COVID-19 infection, such as  kunyit, t emulawak, jahe, kencur, pegagan  and  kelor . To date, herbs utilization for health in Banjar Sambahan remains very limited. This is related to the limited skill in processing herbal drink ( jamu ). This activity aimed to raise participant (PKK women at Banjar Sambahan) knowledge, as well as skills, on producing herbal drinks ( jamu/loloh ) that potentially increase the immunity during COVID-19 pandemic era. This programme was performed by socialization about herbs utilization for health (especially for immunity), accompanied by training (by video) on producing herbal drink and survey for herbal medicine utilization in community. The results of this programme were video, publication on national journal (SINTA indexed) and presentation on national scientific meeting. It can be concluded that this activity supply knowledge and skill for PKK women at Banjar Sambahan in processing herbal drink for maintaining the immunity against COVID-19 infection. Keywords:  covid-19, immune, herbal drink, community service